PENGARUH KEDISIPLINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA XIV DI KOTA MAKASSAR - Rima Iswahyuni Amir; Nurman; Agung Widhi Kurniawan; Romansyah Sahabuddin; Burhanuddin (MANAJEMEN DEWANTARA, 2023)
This study aims to determine the effect of work discipline and work motivation on employee performance at PT Nusantara Plantation XIV Makassar City. The population in this study were all permanent employess, totaling 109 employess. The number of samples us was 53 people using random sampling theory. Data collection techniques are used by using questionnaire description and dissemination methods. The data analysis technique used is multiple linear analysis using stastical product and service solution 25 (SPSS). The results of this study show that the two independent variabeles, namely work discipline (X1) have a positive and partially significant effect on employee performance (Y) and work motivation(X2) have a positive and partially significant effect on employee performance (Y) while work discipline (X1) and work motivation (X2) have a simultaneous positive and significant influence on the dependent variable, namely employee performance (Y).